2019
DOI: 10.1016/j.ijpara.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Chance or choice? Understanding parasite selection and infection in multi-host communities

Abstract: Ongoing debate over the relationship between biodiversity and disease risk underscores the need to develop a more mechanistic understanding of how changes in host community composition influence parasite transmission, particularly in complex communities with multiple hosts. A key challenge involves determining how motile parasites select among potential hosts and the degree to which this process shifts with community composition. Focusing on interactions between larval amphibians and the pathogenic trematode R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…ondatrae preferentially select Ra. catesbeiana larvae in choice trials, despite its overall low susceptibility to infection [48]. Similar 'identity effects' for particular species in diluting infection among focal hosts has also been demonstrated for other disease systems (e.g.…”
Section: Discussionsupporting
confidence: 57%
“…ondatrae preferentially select Ra. catesbeiana larvae in choice trials, despite its overall low susceptibility to infection [48]. Similar 'identity effects' for particular species in diluting infection among focal hosts has also been demonstrated for other disease systems (e.g.…”
Section: Discussionsupporting
confidence: 57%
“…Host age is expected to affect host susceptibility and resistance to parasites (Sackett et at. 2018;Ashby and Bruns 2018;Johnson et al 2019;Izhar et al 2020). Through experimental evidence, our study suggests that variation in host age can drive parasite choice, leading to fundamental differences in parasite burdens among host individuals.…”
Section: Discussionmentioning
confidence: 83%
“…Host age is among the most important and heterogeneous trait driving parasite infections (Woolhouse 1998; Ben-Ami 2019). For example, juveniles or young adults can be more susceptible to infections than old adults (Izhar & Ben-Ami 2015;Ashby and Bruns 2018), which may lead to differences in exposure to parasites (Poulin 2007) and ultimately determine parasite preference/choice (Johnson et al 2019). However, previous studies have shown that older adults are also larger bodied hosts and thus might harbour higher parasite species richness (Kamiya et al 2014;Bolnick et al 2020) and abundance (Poulin 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These fundamental processes are infection , parasite development and pre-transmission survival and together encompass an organism's capacity to transmit infection (Box 1). Exposure should be treated as distinct from competence, because it can be influenced by movements, behaviours and interactions of multiple players in an ecological community, as well as parasite choice (Johnson et al ., 2019 a ) or vector selectivity (Kilpatrick et al ., 2006). Likewise, infectivity (the likelihood of transmission from donor to recipient) depends on the behaviour and susceptibility of a recipient host or vector outside of the host–parasite interaction, so should not be treated as a component of competence.…”
Section: Unpacking Competence: Towards a Unifying Definition And Systmentioning
confidence: 99%
“…On the parasite's side, Ebert (1994) demonstrated that the ability of microsporidians to infect and reproduce within Daphnia decreases as a function of geographic distance between host genotype and parasite genotype. An added dimension to parasite adaptation is parasite choice (Johnson et al ., 2019 a ), which may evolve to strengthen or relax host–parasite encounter rates beyond those expected by density- and frequency-dependent processes alone. As hosts vary in frequency and quality over the landscape, their importance for parasite transmission may also vary, and the potential for local adaptation may make competence an evolutionary dynamic property.…”
Section: Competence As An Emergent Property Of Host–parasite Interactmentioning
confidence: 99%